2020
DOI: 10.1111/jcmm.14920
|View full text |Cite
|
Sign up to set email alerts
|

Circulating adiposity‐related microRNAs as predictors of the response to a low‐fat diet in subjects with obesity

Abstract: Recent studies have revealed the critical role of several microRNAs (miRNAs) in energy homeostasis and metabolic processes and suggest that circulating miRNAs can be used as early predictors of weight loss in the design of precision nutrition. Thus, the aim of this study was to investigate circulating adiposity‐related miRNAs as biomarkers of the response to two specific weight loss dietary treatments. The expression of 86 miRNAs was investigated in plasma of 78 subjects with obesity randomized to two differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 52 publications
0
36
0
Order By: Relevance
“…Interestingly, when we performed IPA analyses of the differential proteome of omental adipose tissue from women with gestational diabetes mellitus (GDM) compared to adipose tissue from control subjects ( 48 ) we found that mitochondrial dysfunction topped the list of differentially expressed pathways (data not shown) further supporting the relationship between high levels of estradiol and metabolic changes. Lastly, body composition may affect metabolic health and as such may alter miR plasma levels as well ( 49 ), although BMI was not significantly affected in transwomen in this study ( Tables 1 and 2 ). Still, future studies should investigate miR-224/452 in relation to body composition changes over time.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, when we performed IPA analyses of the differential proteome of omental adipose tissue from women with gestational diabetes mellitus (GDM) compared to adipose tissue from control subjects ( 48 ) we found that mitochondrial dysfunction topped the list of differentially expressed pathways (data not shown) further supporting the relationship between high levels of estradiol and metabolic changes. Lastly, body composition may affect metabolic health and as such may alter miR plasma levels as well ( 49 ), although BMI was not significantly affected in transwomen in this study ( Tables 1 and 2 ). Still, future studies should investigate miR-224/452 in relation to body composition changes over time.…”
Section: Discussionmentioning
confidence: 68%
“…Ghavami et al demonstrated a significant increase in circulating miR‐375 as well as a significant decrease in KLF5 mRNA expression after 6 weeks of insulin supplementation in diabetic patients 37 . In another study employing RT‐PCR‐based analysis of the effects of diets on miRNA expression, Assman et al reported 7 miRNAs (miR‐130a‐3p, miR‐142‐5p, miR‐144‐5p, miR‐15a‐5p, miR‐22‐3p, miR‐221‐3p and miR‐29c‐3p) as differentially expressed between responders and nonresponders to a low‐fat diet 38 . Kurylowicz et al showed that the expression of SIRT1 in vascular adipose tissue of obese subjects was negatively correlated with the expression of miR‐22‐3p 39 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these skeletal muscle-derived miRNAs have also been detected in the bloodstream [40,[183][184][185][186][187][188][189][190][191][192][193][194][195][196][197][198][199]. However, to date it is unknown whether their circulating levels are modulated during cancer cachexia in humans.…”
Section: Other Skeletal Mirnas Identified In Mouse Models Of Cancer Cachexiamentioning
confidence: 99%